Universal and cross‐cancer prognostic biomarkers for predicting survival risk of cancer patients from expression profile of apoptotic pathway genes. Issue 3 (28th October 2021) - Arora, Chakit; Kaur, Dilraj; Raghava, Gajendra P. S.
Abstract: Numerous cancer‐specific prognostic models have been developed in the past, wherein one model is applicable for only one type of cancer. In this study, an attempt has been made to identify universal or multi‐cancer prognostic biomarkers and develop models for predicting survival risk across different types of cancer patients. In order to accomplish this, we gauged the prognostic role of mRNA expression of 165 apoptosis‐related genes across 33 cancers in the context of patient survival. Firstly, we identified specific prognostic biomarker genes for 30 cancers. The cancer‐specific prognostic models achieved a minimum Hazard Ratio, HRSKCM = 1.99 and maximum HRTHCA = 41.59. Secondly, a comprehensive analysis was performed to identify universal biomarkers across many cancers. Our best prognostic model consisted of 11 genes (TOP2A, ISG20, CD44, LEF1, CASP2, PSEN1, PTK2, SATB1, SLC20A1, EREG, and CD2) and stratified risk groups across 27 cancers (HROV = 1.53‐HRUVM = 11.74). The model was validated on eight independent cancer cohorts and exhibited a comparable performance. Further, we clustered cancer‐types on the basis of shared survival related apoptosis genes. This approach proved helpful in development of cross‐cancer prognostic models. To show its efficacy, a prognostic model consisting of 15 genes was thereby developed for LGG‐KIRC pair (HRKIRC = 3.27, HRLGG = 4.23). Additionally, we predicted potential therapeutic candidates for LGG‐KIRC high risk patients.